Microstructural characterisation of metallic shot peened and laser shock peened Ti–6Al–4V. (15th January 2017) - Lainé, Steven J.; Knowles, Kevin M.; Doorbar, Phillip J.; Cutts, Richard D.; Rugg, David
Abstract: A detailed analysis has been conducted of Ti–6Al–4V processed by metallic shot peening and laser shock peening. Analysis by incremental hole drilling, electron backscattered diffraction microscopy, transmission electron microscopy and transmission Kikuchi diffraction microscopy is evaluated and discussed. The results of this analysis highlight the very different dislocation structures in surfaces processed by these two techniques. Transmission Kikuchi diffraction also has been used to evaluate sub-grains generated by laser shock peening. A notable feature of material processed by laser shock peening is the almost complete absence of deformation twinning, contrasting with the frequent observation of extensive deformation twinning observed in the material processed by metallic shot peening. Graphical abstract: Image 1